Язык и культурa – кaк систeмa кoммуникaции - Aбдуллaeвa, Р.A (FAN va JAMIYAT, 2023)
This article examines the language as a social phenomenon. It cannot be mastered outside of social inter- action, i.e. without communicating with other people. Although the process of socialization is largely based on the imita- tion of gestures - nodding, manners of smiling and frowning - language serves as the main means of transmitting culture.